Manajemen Pemerintahan Daerah dalam Upaya Pemberdayaan UMKM Produk Carica Di Kecamatan Mojotengah Kabupaten Wonosobo - Retnoningsih, Yuyun; ., Kushandajani; Abdurrahman, Wahid (Journal of Politic and Government Studies, 2017)
Management local government in an effort to empowerment SME’s carica products required to be done as activities management of the to achieve a purpose that have been planned. In this activity was conducted using the management function that is planning, organizing, actuating and controlling. Carica fruit is a superior product Regency of Wonosobo, therefore the government makes every effort to empowerment that carica product can compete in domestic market and international market.The results show that local government management in an effort to empowerment SME’s carica product can be concluded already done well but still need to be done synergy so that all program can be realized well. Planning activities have been done well, organizing activities are still needed further deepening for the activities of actuating more focused on human resources and controlling which is the final activity in management is done in the form of evaluation. As for encouraging factors and inhibit factors ; encouraging factors that include: tourism sector and the involvement of various parties ; inhibit factors that include : the low resources, raw materials and technological limitations.Key Words : Management local Government, SME’s